Acute hypobaric hypoxia attenuates the anti-fatigue effects of pitolisant by downregulating the expression of organic cation transporter 1 and P-glycoprotein - Zhao, Gang; Li, Yajuan; Liu, Mengyuan; Chang, Wei; Shen, Hui; Xue, Junhui; Liu, Fengzhou (Frontiers in Pharmacology, 2025)
ObjectiveThis study investigates the effects of acute hypobaric hypoxia (HH) on the anti-fatigue properties of pitolisant and explores the underlying mechanisms. The aim is to provide a theoretical basis for expanding its clinical indications and optimizing its use in individuals exposed to HH conditions.MethodsThe anti-fatigue effects of pitolisant were evaluated using the water maze, novel object recognition, and rotating rod tests. Drug concentrations and dopamine levels were analyzed using High-Performance Liquid Chromatography-Mass Spectrometry/Mass Spectrometry (HPLC-MS/MS). Additionally, gene and protein expression levels of P-glycoprotein (P-gp) and organic cation transporter 1 (OCT1) were assessed to explore the mechanisms by which HH affects pitolisant’s pharmacodynamics.ResultsA 40 mg/kg dose of pitolisant significantly improved learning, memory, cognitive, and motor functions in sleep-deprived mice under HH conditions (P < 0.05). Pharmacokinetic analysis revealed a reduction in pitolisant concentration in the brain under HH conditions. Furthermore, OCT1 protein expression decreased after 1 h and 1 day of HH exposure (P < 0.05), while P-gp expression decreased after 1 h (P < 0.05).ConclusionHH possibly reduced pitolisant’s brain concentration and efficacy by altering the expression of OCT1 and P-gp transporters. A 40 mg/kg dose was necessary for an effective anti-fatigue response. Pitolisant shows potential for supporting circadian rhythm regulation in shift workers and individuals suffering from jet lag. When used under HH conditions, adjusting the dose and frequency may be necessary due to altered pharmacokinetics.